Czy na plantacjach nasiennych zawężamy zmienność genetyczną? Próba odpowiedzi na podstawie analiz mikrosatelitarnego DNA szczepów rosnących na plantacji nasiennej sosny zwyczajnej (Pinus sylvestris L.) z Nadleśnictwa Susz - Przybylski, Paweł (Leśne Prace Badawcze, 2015)
Scots pine ( Pinus sylvestris L.) is the most common species in Poland’s forest stands. The mode of pine stands renovation requires that silviculture practitioners have continuous access to seed banks. Orchard-grown seeds are predicted to constitute an increasingly larger part of the average demand for pine seeds in Poland. Seed orchards, due to a limited number of maternal trees as well as the irregularity of their blooming and pollination, enhance the risk of genetic diversity reduction in planted forest stands. This is of particular importance in the context of dynamic climate change. Markers based on microsatellite DNA fragments are effective tools for monitoring genetic variability. In the present study, three different microsatellite DNA fragments were used: SPAC 12.5, SPAG 7.14 and SPAC 11.4. The main objective of this research was to study genetic variability in one of the biggest seed orchards in Poland, located in the Forest District Susz. The obtained results indicated heterozygosity loss within the orchard, proving the existence of specimen selection effects on genetic variability. Hence, it seems quite important to take account of molecular genetic variability of maternal trees in future breeding strategies.